The Global Online Sexuality Survey: The United States of America in 2011. Issue 3 (September 2015) - Shaeer, Osama; Sheer, Kamal
Abstract : Purpose: The Global Online Sexuality Survey (GOSS) is a world-wide epidemiologic study of sexuality. It was first launched in the Middle East in 2010 and then in the USA in 2011. The current report investigates homosexual orientation and practice. Patients and methods: GOSS was randomly deployed to English-speaking male web surfers in the USA through advertising on Facebook, regardless of surfing preferences. Online surveying provided a confidential and nonconfrontational environment. Results: An overall 27.8% reported sexual desire toward the same sex (male) in varying degrees, of whom 37.5% reported sexual encounters with males (practicing homosexuals; 10.3% of the total sample), mostly in the form of external stimulation, less commonly as anal receptive practice and then as anal insertive practice, in different combinations; 85.3% were egosyntonic and 14.7% were egodystonic; 62.5% of those reporting homosexual desire never had sexual contact with males (nonpracticing/suppressed homosexuals; 17.5% of total participants). Classified as per the Kinsey scale (#2513; #2513), 18.1% reported various grades of homosexual orientation. Conclusion: This is – to our knowledge – the first online survey to address the prevalence of homosexual orientation and practice in the USA, using several investigation methods, discriminating desire from practice, egosyntonic homosexuality from egodystonic, and investigating the pattern of homosexual activity. It is also the first investigation of the relationship between child abuse and homosexuality.